A Critical Discourse Analysis of Nadiem Makarim’s Speech on Merdeka Belajar at the 2024 National Education Day - Febriansyah, Gema; Novita, Rita; Chairina, Melyanda Agustin; Elvonny, Tia Kharina (Journal of Language and Literature Studies, 2024)
This study critically analyzes Nadiem Makarim’s 2024 National Education Day speech, focusing on how language reflects and reshapes power dynamics and ideology within Indonesia’s Merdeka Belajar (Independent Learning) reform initiative. The research seeks to answer two key questions: how does the speech frame educational reform through discourse, and how does it distribute power and convey participatory ideology? Using Fairclough’s Three-Dimensional Model and van Dijk’s Power and Ideology framework, this qualitative study examines the textual, discursive, and social practices within the speech. The findings reveal that the speech strategically emphasizes decentralization, teacher and student empowerment, and cultural values of gotong royong (mutual cooperation) while reframing challenges, such as the pandemic, as opportunities for systemic change. These results suggest that the speech functions as a tool to foster collective responsibility and support for long-term educational reform. The study concludes with recommendations for policymakers to adopt inclusive, culturally resonant discourse to ensure effective communication of reform initiatives. Future research could explore the long-term impact of such discourse on policy implementation across diverse educational contexts.